The mediating effect of self-efficacy on career aspiration and organizational support with subjective career success among Malaysian women managers during the Covid-19 pandemic - Hamzah, Siti Raba'ah; Musa, Siti Nur Syuhada; Mohamad, Norhazlina (Frontiers in Sociology, 2022)
While the lives and jobs of many people have been negatively affected by the Covid-19 pandemic, the question is whether women’s jobs are more vulnerable to the crisis. Lockdowns to curb the pandemic have resulted in many people having to work from home. In this regard, it would be useful to understand the factors that affect career success, especially that of Malaysian women managers. The present study sought to examine the impact of career aspiration and organizational support on subjective career success, as well as the mediating role of self-efficacy in these relationships. The participants comprised 146 Malaysian women managers who had completed an occupational self-efficacy scale, career aspiration scale, as well as perceived organizational support and subjective career success inventory. The results of multiple linear regression indicated that those with high levels of career aspiration and perceived organizational support were associated with subjective career success. Self-efficacy mediated both the relationships. The findings provided a better understanding of women managers’ perception of career success in the service sector.